The psychology of the language learner : individual differences in second language acquisition - Dörnyei, Zoltán (Second language acquisition research., 2005)
Research results over the past decades have consistently demonstrated that a key reason why many second language learners fail--while some learners do better with less effort--lies in various learner attributes such as personality traits, motivation, or language aptitude. In psychology, these attributes have traditionally been called ""individual differences."" The scope of individual learner differences is broad--ranging from creativity to learner styles and anxiety--yet there is no current, comprehensive, and unified volume that provides an overview of the considerable amount of research con.